Healthcare tax credits: financial help to taxpayers or support to higher income and better educated patients? Evidence from Italy - Elenka Brenna (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2017)
In several countries, taxpayers are given the option to detract from gross taxation a share of their out of pocket healthcare expenditure. This paper investigates the use of Healthcare Tax Credits (HTCs) in Italy through the analysis of a panel data which provides information on individual income tax from 2008 to 2014. The study focuses on the disparities emerging in the use of HTCs between Northern and Southern regions: per capita HTCs, either weighted for general population or for the number of claimants, are higher in the North than in the South of Italy. The existing differences in the average income between the two regional clusters may drive to inequalities in the out of pocket expenditure for healthcare services; however, the observed North-South gradient could also reveal possible disparities in the ability of using HTCs, mainly due to socioeconomic factors. A fixed effects OLS model is run to examine the impact of selected socioeconomic variables on regional per capita HTCs, with a particular focus on the role of education. Results corroborate the regressive imprinting of HTCs supported by literature and provide highlights on the role of education in explaining HTCs distribution among regions. Public money is reimbursed to regions where people are on average richer and better educated. More equitable objectives could be reached by allocating the same resources in the provision of services covered by NHS.
Keywords: I14; H31; H51; 330; Health-related tax credits; regional disparities; healthcare access; personal income tax